METODE AL-BUKHARI MENYELEKSI HADIS-HADIS SAHIFAH HAMMAM IBN MUNABBIH - Silviantoro, Noor Ikhsan (Al-MAJAALIS, 2013)
Al-Bukhari selecting hadith from Sahih al-Bukhari hadith 600,000, among which are marwiyyat Sahifah Hammam ibn Munabbih. Scholars state that meets the requirements marwiyyat Sahifah Hammam al-Bukhari, but why only partially narrated? Al-Nawawi suggests four reasons: Due to forget, to be more concise, â??illah, and represented by another hadith. The first two reasons are subjective, while the last two reasons are empirical and impossible to prove. Hazimi believes al-Bukhari terms are hadith first level narrator, sometimes he also took second level if the hadith narrators of hadith narrators do not get the first level in the chapter. To perform the inventory marwiyyat prove Sahifah Hammam in Sahih al-Bukhari. Of the 139 marwiyyat Sahifah Hammam, 129 of them were issued in the al-Jami', 51 narrated through the Hammam and the other disciple, 78 other hadith narrated by Abu Hurayrah student pathways besides Hammam. There are 10 hadiths which are not issued by al-Bukhari, Hadith 8 of them are represented by other companions, one of whom mansukh. Two other hadith that are not excluded because due to â??illah. From data analysis, al-Bukhari Hadith always put the students first at the level of Abu Hurayrah: al-A'raj, Ibn al-Musayyib, Ibn Sirin, and the other, then the traditions Hammam. Thus the conclusion al-Nawawi and al-Hazimi very accurate and fit the facts. Keywords: al-Bukhari, Hadist, Sahifah Hammam.